Drug-resistant epilepsy treated with a vagus nerve stimulator – case report and literature review - Leśniewski, Michał; Brzuchacz, Dominika; Błaszczeć, Patrycja; Miecznikowska, Agata; Siwak, Natalia; Welian-Polus, Iwona; Szukała, Klaudia; Chrościńska-Krawczyk, Magdalena (Journal of Education, Health and Sport, 2024)
The average incidence of epilepsy worldwide is estimated at 7.60 cases per 1,000 inhabitants, with an average annual incidence of 67.77 cases per 100,000 inhabitants. Epilepsy is one of the most common neurological diseases. However, it is not a disease entity, but a set of symptoms that may occur against the background of various morphological and metabolic changes in the brain. Symptoms of epilepsy include epileptic seizures, i.e. temporary disturbances in the bioelectric activity of brain nerve cells. Epilepsy is a brain disorder characterized by a persistent predisposition to trigger seizures, and the condition has neurobiological, cognitive, psychological, and social consequences. Effective treatment of epilepsy may require the use of various methods. In this paper, we would like to present a case report on the treatment of drug-resistant epilepsy using a vagus nerve stimulator (VNS). The described case may prove the effectiveness of treatment of focal drug-resistant epilepsy using vagus nerve stimulation (VNS). Choosing an appropriate, effective method of treating children with drug-resistant epilepsy is crucial; it is especially worth thinking about innovative methods such as VNS.